Macrophages and Pancreatic ductal adenocarcinoma - Habtezion, Aida (Cancer Lett, 2015)
Monocytes and macrophages make up part of the innate immune system and provide one of the first defenses against variety of treats. Macrophages can also modulate the adaptive immune system. Efficient sensing and response to tissue environmental cues highlights the complexity and dynamic nature of macrophages and their plasticity. Macrophages may have divergent roles depending on their polarity and stimulus received. Accumulating evidence demonstrates the critical role played by macrophages in tumor initiation, development, and progression. In this review, we discuss the characteristics of tumor-associated macrophages (TAMs) and their role in pancreatic adenocarcinoma. In addition, we give an overview on recent advances related to the therapeutic implication associated with targeting TAMs in pancreas cancer.